Queer Life(lines) Within the Death of an Archive - Setareh Noorani (Footprint)
In this essay turned collective text-archive, I explore, through proliferating Stieglers thought, epigenetics as the genetic transfer of experience, seeing it as our inherited tools, codes, and processes that enable us to construct radical political alternatives. Similarly, the global West has inherited institutions and their systems – such as the archive – retaining specific perspectives founded on a Eurocentric epistemic model proximate to whiteness, masculinity, and heteronormativity, while obscuring or forgetting Other knowledges. A main question is: who and whose knowledge is in need to be constructed as indispensable, as present outside of the gap? What knowledge constructs whose subjectivity? Part of the confrontation exists of tracing the archive’s outside space, entangling with Other ways of doing that enable us to rethink institutions. This means then partially coming to terms which knowledge and bodies we need to survive collectively and in solidarity. And thus, what urgent, vibrant archives are we already passing on, beyond our own (knowledge) lifespan? This essay-text-archive makes visual the layered and multi-authored process of creating this knowledge resource. It intends to deconstruct and queer the position of the footnote, as archival trace and life’s whisper – with its curator-writer-editors as performing the essential care-work of mediating this archival effort.